2015
DOI: 10.1111/echo.12839
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Consideration for Techniques to Detect and Quantify Blood Flow through Intrapulmonary Arteriovenous Anastomoses: Lessons from Physiological Studies

Abstract: Intrapulmonary arteriovenous anastomoses (IPAVA) are large diameter (>50 μm) vascular conduits, present in >95% of healthy humans. Because IPAVA are large diameter pathways that allow blood flow to bypass the pulmonary capillary network, blood flow through IPAVA (QIPAVA) can permit the transpulmonary passage of particles larger than pulmonary capillaries. IPAVA have been known to exist for over 50 years, but their physiological and clinical significance are still being established; although, currently suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 65 publications
(243 reference statements)
1
17
0
Order By: Relevance
“…Literature clearly indicates that transthoracic contrast echocardiogram (TTCE) is optimal for detecting PAVMs in adults and probably also in the pediatric HHT population, as some studies have shown . It should also be noted however, that this literature does not take into account non PAVM causes of a right‐to‐left shunt . Though very rare, there is a potential risk of ischemic stroke as a complication of TTCEs in patients with significant shunt …”
Section: Introductionmentioning
confidence: 99%
“…Literature clearly indicates that transthoracic contrast echocardiogram (TTCE) is optimal for detecting PAVMs in adults and probably also in the pediatric HHT population, as some studies have shown . It should also be noted however, that this literature does not take into account non PAVM causes of a right‐to‐left shunt . Though very rare, there is a potential risk of ischemic stroke as a complication of TTCEs in patients with significant shunt …”
Section: Introductionmentioning
confidence: 99%
“…In addition to detection of PAVS with an increased frequency in cCVA, it appears that PAVS is “dynamic”. That is, PAVS may occur with increased severity and frequency during “hypoxic” states or during exercise . It is the presence of a previously undetected PAVS that has been noted to be a causative agent for persistent detection of a right‐to‐left shunt after device closure of a PFO …”
Section: Anatomical Associations/false Positive or Negative Pfomentioning
confidence: 99%
“…This filtering role can be compromised, however, by the presence of both intrapulmonary (eg, intrapulmonary arteriovenous anastomoses, IPAVA) and intracardiac (eg, patent foramen ovale, PFO) right‐to‐left shunts . The presence of these pathways does not guarantee that a patient will have a stroke or transient ischemic attack because there are large numbers of otherwise healthy humans, which have either blood flow through IPAVA (~30%) and/or PFO (25%–40%) under resting conditions . Nevertheless, with these pathways present and the propensity for emboli formation in individuals who may be prothrombotic, the opportunity exists for emboli of venous origin to bypass the pulmonary microcirculation.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The presence of these pathways does not guarantee that a patient will have a stroke or transient ischemic attack because there are large numbers of otherwise healthy humans, which have either blood flow through IPAVA (~30%) and/or PFO (25%-40%) under resting conditions. [3][4][5][6][7] Nevertheless, with these pathways present and the propensity for emboli formation in individuals who may be prothrombotic, the opportunity exists for emboli of venous origin to bypass the pulmonary microcirculation. Therefore, IPAVA and PFO may contribute to the etiology of stroke and TIA in some patients.…”
Section: Introductionmentioning
confidence: 99%